Utilization of iodized salt in the production of pickled mango (Mangifera Indica Linn) - Buebos, Mary Jacqueline De Leon
The utilization and the effects of using iodized salt on the quality of pickled green mangoes were assessed. Iodine deficiency disorders (IDD) is currently considered a major nutritional deficiency taht haunt the Philippines and even parts of the industrialized world. Part of the efforts being exerted by the Philippine government is the mandatory implementation of salt iodization nationwide. Local food processors are required to use iodized salt by January, 1996 and the burden of the proof is imposed on the processors themselves. Studies on the utilization of iodized salt in common processed foods such as pickled mango could help the small and medium scale processors coped with this imposed legislation. The first phase of the study focused on the selection of the most acceptable commercial pickled mango formulation. Among 3 local commercial producers of pickled mango, the commercial formulation employed by DECS' Chinese Deli was found to be the most acceptable based on sensory analysis. Objective tests which include physico-chemical and microbiological evaluations were done to compare the pickled mangoes produced by the 3 local manufacturers. Physico-chemical tests of the pickled mango produced by DECS' Chinese Deli showed a pH of 2.80, T.A. (%) of 1.58. as lactic acid, S.S. (%) of 12.0 and NaCl (%) of 9.44. Results of the microbiological examination showed a YMC of 3.6 x 10^4 cfu/g and a TPC of 2.4 x 10^5 cfu/g of sample. Acceptability tests carried out by 40 panelists described the product as having a light green with slight yellow pulp, slightly recognizable fermented odor, a very firm texture and garnered a "like very much" rating for flavor and general acceptability. Pickled green mango with iodized saltwas produced using the commercial formulation employed by DECS' Chinese Deli. Two lots of carabao mangoes were prepared, with the first lot using 10% iodized salt and the other, 10% unfortified salt. For both lots, 1% CaCl2, as firming agent was added within 24-hour brining period. Water was added (with 1% sugar) equal to the weight of mangoes. The pre-drained pickled mango samples were packed in 30° Brix syrup after the 2-week fermentation period held at 10 to 20 °C. The quality of the pickled mango with iodized salt produced in the second phase was evaluated in terms of its objective and sensory attributes. Results of the iodine tests showed that the iodized salt used in the study contained 62.10 μg of iodine/g of salt. Iodine content of pickled mango samples after the 24-hour brining period, exhibited a percentage iodine loss of 93.80%. Undetected were the iodine content of the mango fruit used in the pickled mango production and after the two-week fermentation period. Based on the results, iodine was found to be significantly lost in pickled mangoes, suggesting the highly unstable nature of iodine in acidic, fermented food products. The loss of iodine in he pickled mango sample were attributed to any of the following conditions: (1) too much exposure to moisture; (2) humid environment; (3) exposure to light; (4) acidic nature of the food system; (5) low solubility of KIO3; and (6) possible presence of impurities. Results of the physico-chemical tests of the pickled mango with iodized salt showed a pH of 2.68 with a corresponding T.A. (%) of 1.62, expressed as lactic acid, 11.88& SS and 9.42% NaCl. Incorporation of iodized salt in pickled green mango was found to lower the pH and increase the T.A. (%), S.S. (%) and NaCl (%) content of the pickled mango samples. Microbiological test results showed that the pickled mango with iodized salt had a lower YMC and TPC of 7.8 x 10^3 and 6.9 x 10^4 cfu/g of sample, respectively. The lower microbial count obtained were attributed to the germicidal effect of iodine on a wide variety of microorganisms predominating in pickled green mangoes. Based on a t-test conducted at 5% level of probability, the pickled mango with iodized salt and the control were significantly different from each other in terms of its physico-chemical and microbiological properties. The difference test which was done by 40 panelists indicated that no significant difference existed between the pickled mango samples evaluated at 5% level of probability.